Analysis of the dynamic responses of asphalt pavement based on full-scale accelerated testing and finite element simulation. (28th March 2022) - Liu, Zhen; Gu, Xingyu; Ren, Hua; Zhou, Zhou; Wang, Xiang; Tang, Shi
Graphical abstract: Highlights: Longitudinal strain is analyzed in APT under different loads from various axle weights, temperatures and speeds. The FE model is validated based on the consistency of the time-history curve and the proximity of the peaks of the dynamic response in APT. FE simulation is performed to further analyze the situations (120 km/h, 50 °C) in which actual testing was not available. Abstract: This paper proposes a method of combining full-scale accelerated pavement testing (APT), indoor experiments, and finite element (FE) simulations to analyze and predict the dynamic response of a typical pavement structure with an SMA overlay. First, APT was performed under different loads from various axle weights, temperatures and speeds, and the longitudinal strain was selected as the analysis index. Indoor experiments considering the size effect were used to correct the parameters of the viscoelastic constitutive model. Then, the FE model was validated based on the consistency of the time-history curve and the proximity of the peaks of the dynamic response. Next, dynamic response analysis results indicate that the pavement structure in the influence range of the wheel track is in the strain alternating state of "compression-tension-compression". Increased axle weight and temperature causes an increase in the longitudinal strain at the bottom of the underlayer asphalt, while the situation is reversed for the loading speed. Moreover, the longitudinal strain decreases after pavement overlaying, and the greater the axle weight loading is, the more obvious this trend. The FE analysis method further shows that the compressive stress is mainly concentrated under the wheel track, and it increases and then decreases from the center of the wheel track in the transverse distribution. The shear stress and strain increase and then decrease from the center of the wheel track. As the heavy load increases, the longitudinal strain increases nonlinearly with increasing axial loads, while the maximum shear stress increases linearly. In addition, the simulation results under a high loading speed illustrate that the effect of the loading speed change on the strain is noticeable.